1984
DOI: 10.1902/jop.1984.55.7.419
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Frequent Sugar Intakes on Experimental Gingivitis

Abstract: Few studies have investigated directly the possible role of dietary sugar in the etiology of periodontal disease, although an association between the amount of plaque formed and the frequency of sugar intake has been demonstrated. The purpose of this study was to examine the influence of frequent sugar intakes on experimental gingivitis in young adults. Twenty male dental students took part in a single blind crossover study which involved two 3-week experimental periods with random allocation to high or low su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
43
1
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 12 publications
10
43
1
3
Order By: Relevance
“…Bleeding response to probing was recorded after a 60‐s interval. The bleeding response was classified as nil (0), discrete (1) or profuse (2) (Sidi & Ashley 1984). 2 sets of probing measurements were taken at 15‐min intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Bleeding response to probing was recorded after a 60‐s interval. The bleeding response was classified as nil (0), discrete (1) or profuse (2) (Sidi & Ashley 1984). 2 sets of probing measurements were taken at 15‐min intervals.…”
Section: Methodsmentioning
confidence: 99%
“…A high sucrose intake is associated with increased plaque volume due to the production of extracellular glucans, and there is a strong association between plaque volume and gingivitis. Human intervention studies have shown higher plaque volumes and increased gingivitis with high sucrose diets compared with low sucrose diets 25,26 . However, Gaengler et al 27 pointed out that 'the maximum reduction in sugar in the diet within the limits of practicability is not capable of preventing the development of gingivitis'.…”
Section: Periodontal Diseasementioning
confidence: 99%
“…In contrast, the effects of a long‐term calorie‐restricted diet on experimental periodontitis in a nonhuman primate model demonstrated anti‐inflammatory effects with both reduced levels of gingivitis and reduced active periodontal breakdown compared with a noncalorie‐restricted diet . Similar findings – that frequent sugar intake is associated with gingivitis – are reported in an experimental gingivitis study in humans . In another study, in which humans lived in a stone‐age environment, were placed on a restricted diet from which refined sugars was eliminated and from which oral‐hygiene measures were completely absent, over 30 days demonstrated reduced gingival inflammation, together with probing‐depth reduction and favorable changes in the oral microbiota .…”
Section: Diet and Gingival Inflammationmentioning
confidence: 52%